On the Rim of the Caribbean : Colonial Georgia and the British Atlantic World - Pressly, Paul M. (Book collections on Project MUSE., 2013)
How did colonial Georgia, an economic backwater in its early days, make its way into the burgeoning Caribbean and Atlantic economies where trade spilled over national boundaries, merchants operated in multiple markets, and the transport of enslaved Africans bound together four continents? In this book, the author interprets Georgia's place in the Atlantic world in light of work in transnational and economic history. He considers how a tiny elite of newly arrived merchants, adapting to local culture but loyal to a larger vision of the British empire, led the colony into overseas trade. From this perspective, the author examines the ways in which Georgia came to share many of the characteristics of the sugar islands, how Savannah developed as a "Caribbean" town, the dynamics of an emerging slave market, and the role of merchant-planters as leaders in forging a highly adaptive economic culture open to innovation.